Peramalan Permintaan dengan Pendekatan Marketing Mix pada Produk Sari Apel PT Batu Bhumi Suryatama Menggunakan Artificial Neural Network - Ebenezer M. Sibarani; Wisynu Ari Gutama (Politeknik Kelapa Sawit Citra Widya Edukasi, 2022)
Demand forecasting will provide a solution in planning the number of products to be marketed. Forecasting is a source of information that can be used by companies to prepare themselves in determining the strategy going forward. Demand forecasting in this research is done by marketing mix approach using artificial neural network backpropagation and analysis method used is qualitative and quantitative analysis. The accuracy of forecasting with marketing mix approach using backpropagation neural network is 97.324%. Forecasting results show that the variation of the marketing mix is directly proportional to the change in the volume of demand for apples. Overall increases in distribution costs and promotional costs led to an increase in the number of consumer demand. Decrease in distribution costs and promotional costs also resulted in a decrease in the number of consumer demand.